Life is Beautiful (Życie jest piękne). An Essay About a Series of Radio Documentaries by Głos Ewangelii Foundation - Bachura-Wojtasik, Joanna; Czarnek-Wnuk, Paulina; Sygizman, Kinga (Following Rhetoric, Stylistics and Journalism. A Volume Dedicated to Professor Barbara Bogołębska, 2019)
The article discusses a series of radio documentaries produced by Evangelical Voice (Głos Ewangelii) Foundation. Life is Beautiful has been analyzed and interpreted in categories of subject, use of acoustic elements and themes of religion and god. Moreover, the selected radio programs allowed to indicate a general style of Evangelical Voice Foundation feature documentaries.